SALES OF COSMETICS WITHOUT PERMISSION FROM THE DRUG AND FOOD CONTROL AGENCY (BPOM) IN PERSPECTIVE LAW HEALTH - Khalishah, Salwa (NOMOI Law Review, 2024)
Cosmetics constitute a range of products utilized to enhance and maintain physical appearance. These products include make up, skincare, hair care, nail products, perfumes, and body care items. Cosmetics seem to have become a necessity for men and women to maintain their appearance. However, it is not uncommon to find that there is still a large number of cosmetics circulating that do not have permission from BPOM as the drug and food regulatory body, causing a lot of suspicion among the public. So special attention is needed regarding the distribution of cosmetics without permits based on statutory provisions. This research uses a normative juridical method, which is an approach to legal research that views law as a systematic structure of norms. So this research aims to see the extent to which legislation provides regulations regarding this problem. So it can be seen that the function and duties of BPOM as a drug and food regulatory agency must be able to be more optimal in carrying out its duties and functions. Considering its function, it can be a preventive measure in the circulation of unlicensed cosmetics among the public.